Montréal vert, Montréal bleu - Sénécal, Gilles (Montréal 2001. Visages et défis d'une métropole, 1998)

Montreal and Its Natural Environment - Perron, Normand (Montreal: The History of A North American City, 2018)
Keywords: Climat; Géographie physique; Voie maritime

Montréal et son environnement naturel - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Climat; Géographie physique; Voie maritime

Los parques urbanos de Barcelona y Montréal durante el siglo XIX - García Hermosilla, Carles (Barcelona-Montréal: desarrollo urbano comparado / développement urbain comparé, 1998)
Keywords: Parcs

Les cavités souterraines de Saint-Léonard: coût social d'une contrainte naturelle en milieu urbain - Schroeder, Jacques (Montréal: tableaux d'un espace en transformation, 1992)
Keywords: Quartiers; Saint-Léonard

La terre d'accueil - Marsan, Jean-Claude (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

Le pollen, de la protohistoire à l'ère industrielle. Paysage végétal et société à la pointe à Callière, Montréal, vers 1590 à 1879 - Juteau, Audrée (Université de Montréal, 2019)
Keywords: Flore; Jardins; Paysages; Pointe-à-Callière

Nature's Improvement Wildlife, Conservation, and Conflict in Quebec, 1850-1914 - Ingram, Darcy (Université McGill, 2007)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

Wildlife, Conservation, and Conflict in Quebec, 1840-1914 - Ingram, Darcy (University of British Columbia Press, 2013)
Keywords: Clubs; Faune; Montreal Hunt Club; Natural History Society

The Colonial Landscapes of the Early Town - Coates, Colin M. (Metropolitan Natures: Environmental Histories of Montreal, 2011)

The Herons Are Still Here: History and Place - Dickenson, Victoria (Metropolitan Natures: Environmental Histories of Montreal, 2011)

The Political Ecology of Floods in the Late Nineteenth Century - Boone, Christopher G. (Metropolitan Natures: Environmental Histories of Montreal, 2011)

Surface Water in the Early Nineteenth Century - Fougères, Dany (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Aqueduc; Égouts

The High Ground: Mansions, Mythology, and the Mountain - Macleod, Roderick (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Paysages; Quartiers

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Metropolitan Natures: Environmental Histories of Montreal - Castonguay, Stéphane; Dagenais, Michèle (University of Pittsburgh Press, 2011)

The Urban Horse and the Shaping of Montreal, 1840–1914 - Olson, Sherry (Animal Metropolis: Histories of Human-Animal Relations in Urban Canada, 2017)

Des eaux indésirables: Montréal et ses eaux de surface, 1796-1840 - Fougères, Dany (Revue d'histoire de l'Amérique française, 2006)
Keywords: Égouts

Une ville et son fleuve. Montréal vue/s de l'eau - Dagenais, Michèle (La ville: phénomène de représentation, 2011)

L’épopée de la « Petite rivière » devenue un égout patrimonial à Montréal - Pothier, Louise (Les Cahiers des dix, 2022)
Keywords: Musée Pointe-à-Callière; Patrimoine; Égouts

Slavery, Geography and Empire in Nineteenth-Century Marine Landscapes of Montreal and Jamaica - Nelson, Charmaine A. (Routledge, 2016)
Keywords: Africains; Esclaves; Noirs; Paysages; Peinture

L'évolution du réseau d'élimination des eaux usées à Montréal au 19e siècle - Véronneau, François (Bulletin de l'Association québécoise pour le patrimoine industriel, 1991)
Keywords: Égouts

Cohabitation, exploitation et nuisances à Montréal et à La Nouvelle-Orléans : les relations entre les populations urbaines et animales, 1840-1890 - Gagnon, Benjamin (Université du Québec à Trois-Rivières, 2020)
Keywords: Alimentation; Faune

« Il s'en tuë jusques dans les jardins de Québec ». La place des animaux sauvages dans la ville (Québec et Montréal, 1663-1763) - Riguelle, William (Urban History Review / Revue d'histoire urbaine, 2024)
Keywords: Alimentation; Faune